MODEL PEMBELAJARAN KOOPERATIF STUDENTS TEAM ACHIEVEMENT DIVISION (STAD) DENGAN TUTOR SEBAYA UNTUK MENINGKATKAN PRESTASI BELAJAR PENJASORKES - I Nyoman Neked Suyasa (Widyadari : Jurnal Pendidikan, 2020)
The purpose of this classroom action research was carried out in class V A semester I SD No. 4 Kerobokan 2018/2019 academic year is to improve the learning achievement of Physical Education by using the student team achievement division (STAD) cooperative learning model with peer tutoring strategies. This classroom action research involved 21 research subjects conducted in two cycles through the stages of planning, implementing, observing / observing and reflecting. Learning achievement test is a tool used in collecting research data which is then analyzed using descriptive analysis. The results obtained from this study showed that there was an increase in the ability of students to follow the learning process from an initial average of 70.71 to 74.95 in cycle I and increased to 83.33 in cycle II with 38.10% initial learning completeness in cycle I increased to 66.67% and in cycle II increased to 100%. The conclusion that can be drawn from these results is that the student team achievement division (STAD) cooperative learning model with peer tutor strategies can improve the learning achievement of Physical Education and Health.